(3JYQja Cgd GdJbOjS Hef hUa HGdJOdjSs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefRg Yf GdfbGFV HGdJSHjM hGdJbOjS s
(3BNQgG (B:s
(3hMSHfG Gddg hfYe Gdhcjd hdG Mhd hdG bhI Ei HGddg GdYdi GdYXje s
(3YdjgG NW GHf MLQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B95 s
Keywords: (3GdJGQjNs